The Chongqing vs. Guangdong developmental ‘models’ in post-Mao China: regional and historical perspectives on the dynamics of socioeconomic change - Lim, Kean Fan; Horesh, Niv (Taylor & Francis, 2016)
The Chinese political economy is a dynamic entity constituted by multiple developmental trajectories. Recent debates on two seemingly divergent ‘models’ in the subnational regions of Chongqing and Guangdong has foregrounded the potential contradictions of this dynamism. While existing research has attempted to evaluate these trajectories as outcomes of elite politics or ideological incommensurability, an overlooked but no less important aspect is the connections between these trajectories, Mao-era regulatory policies and the post-1978 system of reciprocal accountability. Synthesizing empirical materials from policy documents, academic commentaries, statistical data and interviews with planners from China, this paper provides a critical evaluation of these connections.